Case Report: Patient-specific three-dimensional printing and computational fluid dynamics in the planning of transcatheter aortic valve replacement for quadricuspid aortic valve - Zhang, Yujing; Cai, Dongxu; Wang, Wei; Du, Hanyan; Gu, Jiwei; Li, Xiaodong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPerforming transcatheter aortic valve replacement (TAVR) in patients with high-risk quadricuspid aortic valve (QAV) may be feasible, but uncertainties remain regarding the development of a comprehensive procedural plan and predicting the outcomes.Case summaryWe report a case of a 70-year-old patient with a high-risk (EuroSCORE II: 11.2%) QAV (type B) and severe aortic regurgitation (regurgitant jet area measuring 9.8 cm2). To avoid high-risk surgery, we selected a 29-mm J-Valve for the transapical TAVR without the occurrence of paravalvular leak based on a patient-specific 3D printed model. Computational fluid dynamics simulations were performed to evaluate the hemodynamic parameters pre- and post-TAVR and showed that the trans-aortic valve pressure gradient decreased from 4.7 mmHg to 3.5 mmHg, the peak trans-aortic velocity decreased from 1.02 m/s to 0.89 m/s, and the low wall shear stress area was increased from 18.92 cm2 to 19.15 cm2. These findings suggest the effectiveness of the TAVR procedure. Based on the simulation results, the procedure was successfully implemented, leading to an improvement in the patient's clinical status.ConclusionThree-dimensional printing and computational fluid dynamics simulations may be valuable tools for planning, assessing procedural outcomes, and evaluating risks in TAVR procedures for patients with QAV.